(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Computer Recorder uses Arduino Board technology to measure temperature, humidity, voltage, and current which are the four parameters of PV output power as performance evaluated with and without cooling media in the form of Perforated Aluminum Plate. Since the voltage provided by the PV module is too high to be used as a receiver for the Arduino, a voltage divider was used to determine the voltage. The DHT22 was used to measure humidity. Finally, the ACS712 module was used to calculate the current, which can detect the current generated by the PV module. Manual measurement is considered inefficient. Therefore we need a real-time data recording device called Datalogger based on Arduino. The Datalogger has a voltage tolerance percentage of 0.025%, a temperature tolerance percentage of 0.08%, and a humidity tolerance percentage of 0.025%. Datalogger is capable of recording a maximum of 5 PV modules simultaneously. Dataloggers are capable of measuring current, voltage, temperature, and humidity. The use of a perforated aluminum plate as a cooling medium can increase the output power of PV modules. It can be seen from the research data, at 11:45 am the average PV output power of P1, P2, P3, P4 are 46.84 W, 52.96 W, 59.29 W, 65.20 W. P4 showed the highest increase the output power of 39.19%.